1992
DOI: 10.1002/eji.1830220622
|View full text |Cite
|
Sign up to set email alerts
|

Immunity after treatment of human schistosomiasis: association between IgE antibodies to adult worm antigens and resistance to reinfection

Abstract: Previous studies in school children have demonstrated the slow development with age of resistance to reinfection after chemotherapy of Schistosoma mansoni infections, and have indicated that inappropriate ("blocking") antibody responses prevent the expression of immunity in young children. The present study was designed to investigate further the nature of the protective responses, by serological studies on a group of 151 S. mansoni-infected individuals resident in an endemic area in Machakos District, Kenya. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
360
4
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(402 citation statements)
references
References 28 publications
(9 reference statements)
36
360
4
2
Order By: Relevance
“…This concept is based on evidence that polyclonal IgE stimulation can suppress specific IgE responses to individual antigens [12][13][14], and can also inhibit the activity of mast cells via a saturation of their Fee receptors [12][13][14][15][16]. In this respeci, in the present study we found an inverse correlation between total and specific )M\i\-Ascaris IgE, and have previously reported the existence of mast cell saturation in these slum children [13.21], This suppression of allergic reactivity may reduce the pathological consequences of immune reactions against the parasite, or may represent a mechanism of parasite evasion, as has been proposed for IgG4 antibodies thai block anlibody-dcpendenl killing of schistosomula by human eosinophils [5,6], Thus, immunity to helminth infeclion may be a balance beiween ihe stimulation of immunologicai effector functions and the activation of blocking mechanisms. These results have potentially important implications for the control of helminthic infections in the community, in that treatment programmes thai are sustained for a sufficient lime lo permit significant reductions in total igE levels lo occur may be more efTeclive in preventing reinfection than sporadic 'one hit* type anthelmint applications.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This concept is based on evidence that polyclonal IgE stimulation can suppress specific IgE responses to individual antigens [12][13][14], and can also inhibit the activity of mast cells via a saturation of their Fee receptors [12][13][14][15][16]. In this respeci, in the present study we found an inverse correlation between total and specific )M\i\-Ascaris IgE, and have previously reported the existence of mast cell saturation in these slum children [13.21], This suppression of allergic reactivity may reduce the pathological consequences of immune reactions against the parasite, or may represent a mechanism of parasite evasion, as has been proposed for IgG4 antibodies thai block anlibody-dcpendenl killing of schistosomula by human eosinophils [5,6], Thus, immunity to helminth infeclion may be a balance beiween ihe stimulation of immunologicai effector functions and the activation of blocking mechanisms. These results have potentially important implications for the control of helminthic infections in the community, in that treatment programmes thai are sustained for a sufficient lime lo permit significant reductions in total igE levels lo occur may be more efTeclive in preventing reinfection than sporadic 'one hit* type anthelmint applications.…”
Section: Discussionsupporting
confidence: 81%
“…where individuals with the highest levels of IgE antibody against either adult worms or egg antigens were less likely to be reinfected with Schistosoma haematobium after treatment than those with the lowest levels. Also, a negative correlation has been demonstrated between TgE against adult worm antigens of 5, man.soni and reinfection [6].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, several immunoepidemiological studies have evidenced a negative correlation between IgE levels and rates of reinfection by the three species of Schistosoma that are pathogen for humans: namely S. mansoni (12,13), S. haematobium (14), and S. japonicum (15). Besides such indirect evidences, a more direct demonstration of the role of IgE in protective immunity was brought both in vitro and in vivo.…”
mentioning
confidence: 99%
“…Aunque en los vertebrados que no producen IgE los mecanismos inmunológicos que controlan la infestación helmíntica son eficientes (al menos, para evitar que alteren la supervivencia de la especie) y en algunos animales se ha observado que la IgE no determina la resistencia, los estudios en humanos y otras especies de mamíferos sugieren que esta inmunoglobulina participa en los mecanismos de protección (22,(54)(55)(56)(57). Sin embargo, es difícil precisar la magnitud en que la IgE habría mejorado la respuesta inmunitaria antihelmíntica, pues aun la inmunidad estéril (eliminación completa de los parásitos en un animal infectado) no es un fenómeno usual; además, no se ha descartado que en los estudios epidemiológicos mencionados, la IgE específica sea sólo una señal asociada a la activación de la inmunidad de tipo 2, la cual, con otros mecanismos efectores, se encargaría realmente de la defensa.…”
Section: Posibles Ventajas Evolutivas De La Respuesta Mediada Por Igeunclassified